Perancangan kursi santai knockdown Dua Jari sebagai solusi furnitur multifungsi untuk hunian modern - Muhammad Pradibta Sedayu Rakasena; DS Drajad Wibowo; Jati Widagdo (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2026)
The demand for functional, flexible, and space-saving furniture is increasing alongside the trend of modern housing characterized by limited land area. As a key furniture element, lounge chairs play a vital role in creating spatial comfort and aesthetics. One widely sought-after approach is the knockdown design, a furniture system that can be easily assembled, disassembled, and relocated. This study aims to design a knockdown lounge chair that not only fulfills the need for multifunctional furniture but also supports a dynamic modern lifestyle. The Design Thinking method was employed to ensure the final product aligns with user needs and preferences, involving five main stages: Empathize, Define, Ideate, Prototype, and Test. Visually, the 'Dua Jari' (Two Fingers) concept draws inspiration from human hand gestures, symbolizing balance and stability. This knockdown lounge chair meets multifunctional criteria through an adaptive seating unit that functions as a conventional lounge chair when attached and as floor seating (lesehan) when detached. Trials involving 50 respondents indicated that 54% of users preferred the knockdown system due to its mobility and space efficiency. In conclusion, the application of the Design Thinking method effectively produces furniture that is relevant to urban community needs while supporting the creation of comfortable, practical, and sustainable living spaces. Published Date: 2026-07-22